Flo & Wendell - William Wegman (New York , NY Dial Books for Young Readers, 2013)
Easy-to-read text and photographs of dogs reveal the challenges of life in a family with a brother and sister who do not always get along well together.
Keywords: Brothers and sisters -- Juvenile fiction. Families -- Juvenile fiction